Attractive Equals Smart? Perceived Intelligence as a Function of Attractiveness and Gender - Murphy, Austin; Shattuck, Britney; McMickle, Kaileen (My University, 2013)
Previous research suggests that people who are attractive are perceived as more friendly, agreeable, and intelligent than are people who are unattractive. Given the importance people attach to intelligence for social, educational, and hiring decisions, the purpose of this study was to determine whether attractiveness affects people's impressions of others' intelligence.
Color poster with text, images, and graphs.
Keywords: Attractiveness; Posters; Intelligence